Barriers and Coping Strategies among Obese and Overweight Learners: Sequential Explanatory Study - Angeles, Princess Jamailah P.; Cruz, Mikaela Yumi S.; Mendoza, Cyril B.; Pamintuan, Marianne D.; Lacson, John Carlo G.; Ignacio, Kate Rhielyn L.; Espinosa, Dexter B.; Galang, John Renus F. (Future Science / FSH-PH Publications, 2024)
his study aims to assess the key barriers to physical activity among overweight and obese adolescents, discovering that the most significant obstacles are a lack of time, different priorities, and a poor perception of one's body. A mixed method sequential explanatory design was used in the study which involves 50 respondents and 8 outliers in one of the public senior high schools in Cluster 1, Division of Pampanga. These findings are consistent with broader research, which shows that time constraints, low motivation, and self-consciousness pose typical challenges for those dealing with weight concerns. Interestingly, the study finds that social support from friends is the preferred coping strategy, implying a preference for emotional comfort over creative solutions. Despite exhibiting good internal problem-solving skills in planning and goal setting, there is a lack of confidence in execution. Furthermore, preferred avoidance coping mechanisms, such as daydreaming and fantasizing, indicate a preference for emotional distance and self-soothing over direct confrontation. The study underlines the value of building self-acceptance and engaging in the present moment as potential alternatives to daydreaming. It also identifies possible issues such as low self-esteem and a desire to escape reality. Notably, overweight and obese learners face different physical and psychological difficulties. The study points out the importance of peer support in coping techniques, as students rely greatly on peers for emotional support, which inspires emotions such as belonging and appreciation. Lastly, learners indicate a stronger willingness to get involved with organized activities such as sports, recognizing the potential benefits of improving physical fitness. It is recommended to further investigate the roles of peer support and sport program and how they affect obese and overweight students. Additionally, it is also recommended to explore the metal health aspects.